Microscopic and macroscopic comparisons of 0.223 soft point and full metal jacket ammunition with bos taurus scapulae as a proxy to human flat bones. Issue 5 (30th May 2020) - Taylor, Seth C; Kieser, D C; Hammer, N; Pullen, A; Hooper, G
Abstract : Background: The prevalence of civilian 0.223 ammunition is widespread. Due to low costs and the same dimensions as a 5.56×45 mm North Atlantic Treaty Organization, this round is exceptionally popular. However, recent mass shootings have employed soft point (SP) expanding ammunition to cause grievous wounds compared with military full metal jacket (FMJ) rounds that do not rapidly expand on impact. Methods: The aim of this given study is to compare FMJ and SP rounds to determine if there are diagnostic differences between the bullet types in the wounds inflicted to flat bones. Bos taurus scapulae were used for 25 m simulated cranial gunshot injuries. Scanning electron microscopy was employed to assess the difference in wound morphology and elemental analysis between SP and FMJ rounds. Results: Entrance and exit wound morphology change significantly between the two different types of ammunition as seen with circumferential delamination which is indicative of FMJ rounds and is not seen with the softer SP hunting rounds. Lead staining of the entrance wound is visible on only the SP rounds. Conclusion: Gunshot flat bone wound morphology is distinctively different between SP and FMJ rounds. Circumferential delamination is only seen with FMJ due to the hardness of the round. Lead staining is only seen with SP rounds due to bullet composition.